Pelaksanaan Supervisi Akademik dalam Rangka Meningkatkan Profesionalitas Guru di SMP Islam Karawang - Fitri Indah Lestari; Undang Ruslan Wahyudin; Taufik Mustofa (FONDATIA, 2022)
In the development of education today emphasizes improving the quality of education, therefore it is necessary to improve the quality of all components contained in the education system, both in terms of quality and quantity. The teacher is seen as the main key because he is the one who interacts directly with his students when teaching and learning activities take place. Teachers act as professional educators with the main task of educating, teaching, guiding, directing, training, assessing and evaluating students in formal or non-formal education. Supervision is a supervisory activity carried out by superiors to assist teachers in critically assessing the performance of the teaching process. The purpose of supervision is so that the implementation of tasks is in accordance with the provisions, procedures and orders that have been set. This study uses a qualitative method with a descriptive approach. The process of collecting data using the unstructured interview method. The results of this study indicate that the implementation of academic supervision at SMP Islam Karawang has been carried out well. However, there are still some teachers who do not want to carry out such supervision. The implementation of supervision in improving the professionalism of teachers is very influential, because from the implementation of the supervision supervisors can find out how to build a better quality of education